1994
DOI: 10.1007/bf01974087
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human lactoferrin in milk of transgenic mice

Abstract: The expression of human lactoferrin (hLF) in the milk of transgenic mice is described. Regulatory sequences derived from the bovine alpha S1-casein gene were fused to the coding sequence of the hLF cDNA and several lines of transgenic mice were generated. Human LF RNA was detected exclusively in the mammary gland of lactating females and only after the onset of lactation. No aberrant RNA products could be detected using northern blotting and primer extension analysis. The hLF concentrations in the milk ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 36 publications
5
54
1
Order By: Relevance
“…The highest amount of pLF (106 mg/L) was found in progenies of mouse line Tg-pLF-33; this high level of pLF production was stably maintained through 10 generations. The pLF level in progenies of line 33 was significantly higher than the levels found in the human LF transgenic mice reported previously (25).…”
Section: Discussioncontrasting
confidence: 70%
“…The highest amount of pLF (106 mg/L) was found in progenies of mouse line Tg-pLF-33; this high level of pLF production was stably maintained through 10 generations. The pLF level in progenies of line 33 was significantly higher than the levels found in the human LF transgenic mice reported previously (25).…”
Section: Discussioncontrasting
confidence: 70%
“…hLf-transgenic mice (line 2261) and wild-type littermates (strain B6CBA) generated as previously described (16,17) were used to establish a colony at Glasgow University (Glasgow, U.K.). For the CIA model, the transgenic mice were backcrossed on to the DBA/1 background and used after six backcrosses.…”
Section: Animalsmentioning
confidence: 99%
“…Many studies have demonstrated that recombinant proteins can be produced in milk, including human IGF-1 (Zinovieva et al, 1998), hGH (Devinoy et al, 1994), human lysozyme (Lee et al, 1998), human lactoferrin (Platenburg et al, 1994), human erythropoietin (Sohn et al, 1999), human parathyroid hormone (Rokkones et al, 1995), and coagulation factor VIII (Chrenek et al, 2007).…”
Section: Use Of Genetically Modified Animals In the Production Of Biomentioning
confidence: 99%
“…Through selective promoters for the mammary gland, such as αs1-casein (Platenburg et al, 1994;Zinovieva et al, 1998) and whey acid protein -WAP (Devinoy et al, 1994;Rokkones et al, 1995), gene expression can be targeted to the mammary gland, with the release of the desired protein in the milk.…”
Section: Use Of Genetically Modified Animals In the Production Of Biomentioning
confidence: 99%